Hydrogen in single-crystalline anatase TiO2 - Lavrov, Eduard V.; Chaplygin, Igor; Herklotz, Frank; Melnikov, Vladlen V.; Kutin, Y. (Journal of applied physics)
Titanium dioxide (TiO2, also known as titania) has attracted a great deal of attention since the discovery of photocatalytic splitting of water under ultraviolet light exposure by Fujishima and Honda. Three modifications of TiO2 are known to occur in nature: rutile, brookite, and anatase, of which only the first is a stable polymorph of bulk titania. The contribution of the surface free energy, however, makes anatase a stable polymorph at the nanometer scale. Compared to rutile, anatase has a longer carrier lifetime and exciton diffusion length, higher electron mobility, and is an order of magnitude more efficient in photocatalysis, which makes it a material of choice for a variety of applications. Hydrogen is a common impurity in TiO2 with a strong impact on its electrical and optical properties. In this Perspective, we discuss the application of IR absorption, Raman scattering, electron paramagnetic resonance, and ab initio theory to get insight into the properties of hydrogen in bulk single-crystalline anatase. In particular, interstitial hydrogen, hydrogen substituting for oxygen, the nature of hidden species, as well as complexes formed by hydrogen with acceptors are considered. Published under an exclusive license by AIP Publishing.